The Research of Periodic Solutions of Time-Varying Differential Models. (16th April 2014) - Liu, Wenjun; Pan, Yingxin; Zhou, Zhengxin
Abstract : We have studied the periodicity of solutions of some nonlinear time-varying differential models by using the theory of reflecting functions. We have established a new relationship between the linear differential system and the Riccati equations and applied the obtained results to discuss the behavior of periodic solutions of the Riccati equations.